The Building Students’ Morals through Routine Dhikr Rotibul Al-Haddad Activities at Ma'arif Islamic Boarding School NU Metro Lampung - Nanda Jafar Sidik; Ikhwan Aziz Q; Rina Mida Hayati (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to determine the role of Dhikr Ratib al-Haddad in the moral development of students at the Ma'arif NU Metro Lampung Islamic Boarding School. In the charming city of Metro, the Ma'arif Nahdlatul Ulama Islamic Boarding School routinely holds dhikr Ratib al-Haddad. In an effort to instill moral values ​​in students, educators at the boarding school not only guide them in memorizing and practicing dhikr, but also apply various strategies to encourage them to behave nobly, both inside and outside the boarding school environment. Dhikr Ratib al-Haddad is one of the most widely practiced and widespread practices among Muslims. This study was taken from the problem that there are still many students who have bad morals, such as speaking rudely, bullying, and disobeying the rules of the boarding school. This study is a qualitative study. The data collection technique is through observation, interviews, and documentation. The subjects of the study were ustadz, students and administrators of PP Ma'arif NU Metro Lampung. The data validity test uses triangulation. The data analysis technique is data reduction, drawing conclusions and presenting data to determine the role of Dhikr Ratib al-Haddad in fostering the morals of students. The results of this study increase awareness of the presence of Allah SWT, develop positive traits such as patience, gratitude, and humility, and form a better character of students.